The Effect of Earnings Per Share and Return on Equity on Share prices: The Moderating Role of Dividen Policy in Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX) : JEL Classification: G11, G12, G32, G35, L85 - Nurul Hikmah; Jannati Tangngisalu; Nuramal Nuramal (Newinera Publisher, 2026)
This study aims to analyze the effect of Earning Per Share (EPS) and Return on Equity (ROE) on share prices with dividend policy as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange for the period 2020-2024. This study uses a quantitative approach with panel data regression methods. The research population consists of 91 companies. The research sample was obtained through purposive sampling, resulting in 19 companies that satisfied the research criteria. Data analysis was performed using Eviews 13 software through testing the best model selection with Chow test and Hausman test resulting in the Fixed Effect Model (FEM) as the best model. The results of the research show that Earning Per Share (EPS) has a positive and significant effect on share prices, while Return on Equity (ROE) does not have a significant effect on share prices. In addition, dividend policy is unable to moderate the effect of EPS and ROE on share prices. These findings indicate that EPS is one of the main determinants in determining share prices, while ROE and dividend policy are not yet significant factors in affecting share prices in the property and real estate sector on the Indonesia Stock Exchange for the period 2020-2024.